International experience in preventing and combating corruption as a key tool for reforming Ukraine’s anti-corruption policy - Hryshchuk, Maksym (Actual problems of law (Aktual’ni problemi pravoznavstva), 2021)
The article analyzes the international experience in preventing and combating corruption. A comparison of the main ways of combating corruption of individual foreign countries is made. The purpose of the article is to carry out a general analysis of the experience of implementing the anti-corruption policy of a number of European Union countries and to develop proposals for improving the political mechanisms for combating corruption in Ukraine. Successful implementation of Ukraine’s tasks in the field of preventing and combating corruption, provided for in the Association Agreement with the European Union, including prevention and fight against corruption, both in the private and public sectors, formation of effective anti-corruption policy, creation and coordination of detection and anti-corruption. It should be emphasized that the newly created mechanism for preventing and combating corruption must meet the international standards of such bodies. The main successful factors in combating corruption approved by the international community are identified, including: legislative regulation of government officials, establishing a clear system of accountability for violations of anti-corruption legislation, openness in the activities of officials, implementation of effective socio-economic and political reforms, implementation education for civil servants; creation and implementation of social programs and educational campaigns on corruption, as well as the organization of anti-corruption seminars, conferences with the participation of governmental, scientific and non-governmental experts. Such developments can be used in the practice of individual government agencies in the fight against corruption, as well as in the development of regulations aimed at reducing the impact of corruption in public administration.